Call for Participation – Workshop Re-thinking education in the digital age. Meaningful perspectives for future citizenship: 27.-29.04.2023 (Zoom/Universität Hamburg) - Kaiser-Müller, Katharina (Medienimpulse, 2022)
Die Konferenz findet vom 27. April bis 29. April 2023 online via Zoom statt. Forschende aller Fachrichtungen sind eingeladen, ihren Antrag bis 15.12.2022 einzureichen. The conference will take place online via Zoom from April 27 to April 29 2023. We invite researchers from all disciplines, to send their proposal till 15.12.2022.